On convolution of functions in angular domains - Dilnyi, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain analogs of the Parseval theorem, convolution theorem, and some other properties of the convolution of functions from the Hardy – Smirnov spaces in an arbitrary convex unbounded polygon.